Association of catalase polymorphisms with primary open-angle glaucoma in a Chinese population. (2nd January 2018) - Gong, Bo; Shi, Yi; Qu, Chao; Ye, Zimeng; Yin, Yilin; Tan, Chang; Shuai, Ping; Li, Jing; Guo, Xiaoxin; Cheng, Yilian; Yang, Zhenglin; Lin, Ying; et al.
ABSTRACT: Purpose: Many genes have been associated with primary open-angle glaucoma (POAG). This study was conducted to investigate whether catalase ( CAT ) polymorphisms play a significant role in POAG in a Chinese population. Methods: A cohort of 416 unrelated POAG patients and 997 unrelated control subjects was included in this case–control association study. CAT functional single-nucleotide polymorphisms (SNPs), including rs1001179, rs7943316, and rs769217, were genotyped by SNaPshot method. The genotype and allele frequencies were evaluated using the χ 2 tests. The linkage disequilibrium (LD) and haplotype block structure association were examined using the program Haploview (Broad Institute, Cambridge, MA). Results: There was a statistically significant difference for CAT functional SNP rs769217 between POAG cases and controls in the allelic model ( p = 0.004, OR = 1.27, 95% CI 1.08–1.49). At this SNP, the allele frequency of the C allele in POAG cases was 0.587, which was higher than that in controls (0.528). However, no association was found for rs1001179 and rs7943316 with POAG. Pairwise LD analysis showed high LD between rs769217 and rs7943316 ( D ' = 0.857, r 2 = 0.252, confidence bounds 0.71–0.93). After the association analysis for haplotype block structure generated from rs769217 with rs7943316, the data showed no significant association between the cases and controls. Conclusions: This study showed that CAT functional SNP rs769217 was significantly associated with POAG, implying that the CAT gene variants may play a role in the pathogenesis of POAG in the Chinese population.